The influence of altered thyroid state on gastrointestinal motility in rats - (:unkn) unknown (My University, 2000)
Objective: Gastrointestinal symptoms frequently accompany thyroid dysfunction. Previous reports on the relationship between the thyroid status and the gut have conflicting results regarding gastric emptying and only a few experimental studies on colonic motility are present. This study was therefore designed to examine thyroid hormone status on gastric emptying and to evaluate small intestinal and colonic motility in experimental hypo/hyperthyroidism in the rat. Methods: Wistar-Albino rats (220-280 g) of both sexes were randomly treated with either Propylthiouracil (20 mg/kg/day, ip, 2 weeks; hypothyroid group) or T3 (1 mg/kg/day, ip, 7 days; hypertyroid group). Evaluation for daily food intake, gastric emptying, intestinal transit and colonic motility was performed. Results: Daily food intake, fecal pellet number and gastric emptying rate were significantly reduced in hypothyroid rats. Both the daily stool volume and the number of fecal pellets were significantly higher in the hyperthyroid rats, whereas intestinal transit in 30 minutes remained unchanged both in the hyperthyoid and hypothyroid rats compared to control group. Conclusion: The data from our experiments indicate that deviations from the normal euthyroid status in either direction principally affects colonic motility. Hypothyroidism seems to act in a broader spectrum, suggesting an overall inhibition in the gut motility.
Keywords: Colon; Gastric emptying; Gastrointestinal motility; Rat; Thyroid hormones